(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Patients with Spinal Cord Injuries (SCI) are confronted with motor and sensory deficits as well as bladder, bowel and sexual dysfunction, which lead to a fundamental change of life. Because of the extensive medical, emotional and social consequences of the SCI, multidisciplinary management is essential. This study focuses on the functional outcome after a spinal cord injury. Methods: This was an observational study done during a period of 6 months from July 2007 to December 2007 among paraplegic spinal cord injured patients, admitted in the Neurosurgery Department and attended in the Department Physical Medicine and Rehabilitation, Chittagong Medical College, Chittagong. A total of 50 patients were selected for the study. Sampling technique was purposive and different scores and followup findings were collected and analyzed by Statistical Package for Social Science (SPSS-15) P value < 0.05 was considered as significant. Results: Mean age of study population was 32.7 years with all patients were between 18 to 55 years age range. Male and female ratio was 9:1. Maximum respondents were day labourer 36.0%, followed by 34.0% other different types of occupation, 10.0% business man, 8.0% service holder, 8.0% housewife and 4.0% student. Fall from height was the major cause of spinal cord injury of the present study group followed by Road Traffic Accident (RTA). Out of all patients 50.0% had urinary incontinence, 44.0% hadbowel incontinence, 46.0% had spasticity, 34.0% had hypotension and 4.0% had bed sore. At pretreatment stage mean (±SD) FIM score of the patients was 92.5 and discharge 107.32. (p <0.05). Spasticity of the patients was 2.6±1.55 at pretreatment stage and after six weeks of treatment mean (±SD) spasticity was reached at 1.96±1.07 (p <0.05). Visual analog scale was used to measure the severity of the pain. At pretreatment stage mean (±SD) pain score of the patients was 5.7±1.07 after six weeks of treatment mean (±SD) pain score was reached at 2.2±0.88 (p <0.05). At pretreatment stage mean (±SD) ASIA score of the patients was 3.0±0.81. After one week of treatment mean (±SD) ASIA score was reached at 3.12±0.72 and after six weeks at 3.38±0.69. ANOVA test was revealed statistical significant difference among groups in term of ASIA score of different treatment stages (F value=3.42, p value =0.035). Conclusion: For SCI rehabilitation program like physical therapy, occupational therapy, orthosis, gait retraining and management of complications make significant improvement in the term of FIM score, ASIA score, muscle weakness pain and spasticity which is proved by current study. So rehabilitation program is the only hope of spinal cord injury patients and physiatrist have important role to achieve the goals of functional outcome in paraplegic patient from spinal cord injury. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 52-56